From light neutrino decay phenomenology to muon neutrino cross-section measurement at MINERvA experiment - Ascencio Sosa, Marvin Vladimir (2022)
This thesis tackles two essential topics of neutrino physics: neutrino decay and neutrino cross-section measurement. First, the invisible and visible neutrino decay is analyzed through a phenomenological approach, considering future long-baseline neutrino experiments such as DUNE and a hypothetical neutrino beam toward the ANDES laboratory. The study takes into account the νμ and νe disappearance and appearance, respectively, for both FHC and RHC flux modes. The results showed a negligible matter effect for DUNE but significantly more notable at ANDES. At 90% C.L., the sensitivity to the decay parameter α3 can be as small as 2 × 10−6 eV2 for a chosen coupling. The impact of neutrino decay in the determination of θ23 and δCP were also shown. Second, the double-differential cross-section measurement for νμ-carbon interactions with three-momentum transfer |q| < 1.2 GeV obtained with medium energy exposures in the NuMI beam at MINERvA experiment are reported. The measurement is presented as a function of |q| and Eavail and reviews different interaction models and nuclear effects along quasi-elastic to resonance processes to define a new model for a better agreement. The double differential cross sections are compared to the MnvTunes, GENIE, and NuWro predictions.